2018
DOI: 10.1007/978-3-319-93445-7_31
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Fingers’ Limitation of Texture Density Perception on Ultrasonic Haptic Displays

Abstract: Recent research in haptic feedback is motivated by the crucial role that tactile perception plays in everyday touch interactions. In this paper, we describe psychophysical experiments to investigate the perceptual threshold of individual fingers on both the right and left hand of right-handed participants using active dynamic touch for spatial period discrimination of both sinusoidal and square-wave gratings on ultrasonic haptic touchscreens. Both one-finger and multi-finger touch were studied and compared. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…These results can be interpreted to mean that when there is lateral finger movement, participants needed a similar amount of electrovibration force for each moving finger for sensory detection. Such a phenomenon has also been observed in previous studies conducted with a variety of other haptic devices [29,30].…”
Section: Two-finger Interactionssupporting
confidence: 81%
“…These results can be interpreted to mean that when there is lateral finger movement, participants needed a similar amount of electrovibration force for each moving finger for sensory detection. Such a phenomenon has also been observed in previous studies conducted with a variety of other haptic devices [29,30].…”
Section: Two-finger Interactionssupporting
confidence: 81%
“…Our current system has limited support for roughness modulation on a small area of the user's skin, specifically the fingerpad, and it is challenging to expand it to cover larger areas like the palm. However, existing research [75] has shown that the index finger and thumb are the most sensitive for haptic perception, suggesting the possibility of using multiple finger-worn haptic devices to support more manipulation gestures in MR environments. In the future, we plan to expand our exploration of roughness modulation to include more types of materials, such as resin or ABS material, as we showed in Fig.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Thus far, most of the studies on tactile perception conducted on these devices were focused on perception thresholds of friction, size or sharpness (Biet et al, 2007;Samur et al, 2009;Kalantari et al, 2016;Kalantari et al, 2018b;Kalantari et al, 2018a). In the context of interaction design however, many opportunities will arise from the ability of rendering tactile textures that provide users with specific perceptual sensations (i.e.…”
Section: Related Workmentioning
confidence: 99%